Buprenorphine + naloxone plus naltrexone for the treatment of cocaine dependence: the Cocaine Use Reduction with Buprenorphine (CURB) study. (21st April 2016) - Ling, Walter; Hillhouse, Maureen P.; Saxon, Andrew J.; Mooney, Larissa J.; Thomas, Christie M.; Ang, Alfonso; Matthews, Abigail G.; Hasson, Albert; Annon, Jeffrey; Sparenborg, Steve; Liu, David S.; McCormack, Jennifer; et al.
Abstract: Aims: To examine the safety and effectiveness of buprenorphine + naloxone sublingual tablets (BUP, as Suboxone ® ) provided after administration of extended‐release injectable naltrexone (XR‐NTX, as Vivitrol ® ) to reduce cocaine use in participants who met DSM‐IV criteria for cocaine dependence and past or current opioid dependence or abuse. Methods: This multi‐centered, double‐blind, placebo‐controlled study, conducted under the auspices of the National Drug Abuse Treatment Clinical Trials Network, randomly assigned 302 participants at sites in California, Oregon, Washington, Colorado, Texas, Georgia, Ohio, New York and Washington DC, USA to one of three conditions provided with XR‐NTX: 4 mg/day BUP (BUP4, n = 100), 16 mg/day BUP (BUP16, n = 100, or no buprenorphine (placebo; PLB, n = 102). Participants received pharmacotherapy for 8 weeks, with three clinic visits per week. Cognitive behavioral therapy was provided weekly. Follow‐up assessments occurred at 1 and 3 months post‐intervention. The planned primary outcome was urine drug screen (UDS)‐corrected, self‐reported cocaine use during the last 4 weeks of treatment. Planned secondary analyses assessed cocaine use by UDS, medication adherence, retention and adverse events. Results: No group differences were found between groups for the primary outcome (BUP4 versus PLB, P = 0.262; BUP16 versus PLB, P = 0.185). Longitudinal analysis of UDS data during the evaluation period using generalized linear mixed equations found a statistically significant difference between BUP16 and PLB [ P = 0.022, odds ratio (OR) = 1.71] but not for BUP4 ( P = 0.105, OR = 1.05). No secondary outcome differences across groups were found for adherence, retention or adverse events. Conclusions: Buprenorphine + naloxone, used in combination with naltrexone, may be associated with reductions in cocaine use among people who meet DSM‐IV criteria for cocaine dependence and past or current opioid dependence or abuse.